Impact of polymorphisms in microRNA biogenesis genes on colon cancer risk and microRNA expression levels: a population-based, case-control study. Issue 1 (December 2016) - Mullany, Lila; Herrick, Jennifer; Wolff, Roger; Buas, Matthew; Slattery, Martha
Abstract Background MicroRNAs (miRNAs) have been implicated in the incidence and progression of cancer. It has been proposed that single nucleotide polymorphisms (SNPs) influence cancer risk due to their position within genes involved in miRNA synthesis and regulation. Methods Genes directly and indirectly involved in miRNA biogenesis were identified from the literature. We then identified SNPs within these regions. Using genome-wide association study data we evaluated associations between biogenesis-related SNPs with colon cancer risk and their corresponding mRNA expression in normal colonic mucosa and carcinoma and difference in expression between the two tissues. SNPs that were associated with either altered colon cancer risk or with mRNA expression were evaluated for associations with altered miRNA expression. Results Eleven SNPs were associated (P < 0.05) with colon cancer risk, and two of these variants remained significant after correction for multiple comparisons (PHolm < 0.05): rs1967327 (PRKRA ) (ORdom = 0.78, 95 % CI 0.66–0.92) and rs4548444 (MAPKAP2 ) (ORrec = 1.67, 95 % CI 1.12–2.48). Of these two SNPs, rs4548444 (MAPKAP2 ), was associated with significantly altered miRNA expression levels in normal colonic mucosa, with nine miRNAs upregulated among individuals homozygous rare (GG) for rs4548444. One SNP associated with cancer prior to adjustment for multiple comparisons, rs11089328 (DGCR8 ), was associated with altered levels of hsa-miR-645 in differential tissue under the dominant model. Three SNPs, rs2740349 (GEMIN4 ) in carcinoma tissue, and rs235768 (BMP2 ) and rs2059691 (PRKRA ) in normal mucosa, were significantly associated with altered mRNA expression levels across genotypes after multiple comparison adjustment. Rs2740349 (GEMIN4 ) and rs235768 (BMP2 ) were significantly associated with the upregulation of six and nine individual miRNAs in normal colonic mucosa, respectively. Conclusion Our data suggest that few of the SNPs in biogenesis genes we evaluated alter levels of mRNA transcription or colon cancer risk. As only one SNP both alters colon cancer risk and miRNA expression it is likely that SNPs influencing cancer do not do so through miRNAs. Because the significant SNPs were associated with downregulated mRNAs and upregulated miRNAs, and because each SNP was associated with unique miRNAs, it is possible that other mechanisms influence mature miRNA levels.